Association of the Protein-Quality-Control Protein Ubiquilin-1 With Alzheimer’s Disease Both in vitro and in vivo - Zhang, Can; Inamdar, Shivangi M.; Swaminathan, Swathi; Marenda, Daniel R.; Saunders, Aleister J. (Frontiers in Neuroscience, 2022)
Alzheimer’s disease (AD) belongs to a class of diseases characterized by progressive accumulation and aggregation of pathogenic proteins, particularly Aβ proteins. Genetic analysis has identified UBQLN1 as an AD candidate gene. Ubiquilin-1 levels reduce with AD progression, suggesting a potential loss-of-function mechanism. The ubiquilin-1 protein is involved in protein quality control (PQC), which plays essential roles in cellular growth and normal cell function. Ubiquilin-1 regulates γ-secretase by increasing endoproteolysis of PS1¬, a key γ-secretase component. Presently, the effects of ubiquilin-1 on cellular physiology as well as Aβ-related events require further investigation. Here, we investigated the effects of ubiquilin-1 on cellular growth and viability in association with APP (amyloid-β protein precursor), APP processing-related β-secretase (BACE1; BACE) and γ-secretase using cell and animal-based models. We showed that loss-of-function in Drosophila ubqn suppresses human APP and human BACE phenotypes in wing veins and altered cell number and tissue compartment size in the wing. Additionally, we performed cell-based studies and showed that silencing UBQLN1 reduced cell viability and increased caspase-3 activity. Over-expression of UBQLN1 significantly reduced Aβ levels. Furthermore, pharmacological inhibition of γ-secretase increased ubiquilin-1 protein levels, suggesting a mechanism that regulates ubiquilin-1 levels which may associate with reduced Aβ reduction by inhibiting γ-secretase. Collectively, our results support not only a loss-of-function mechanism of ubiquilin-1 in association with AD, but also support the significance of targeting ubiquilin-1-mediated PQC as a potential therapeutic strategy for AD.